The Sacred and its Scholars: Comparative Methodologies for the Study of Primary Religious Data - Idinopulos; Yonan (Editors) (Brill, 1996)
Preliminary Material /Thomas A. Idinopulos and Edward A. Yonan -- Preface /Thomas A. Idinopulos and Edward A. Yonan -- Sacrality as Integrity: “Sacred Order” as a Model for Describing Religious Worlds /William E. Paden -- Zionism, Brahminism and the Embodied Sacred: What the Durkheimians Owe to Sylvain-Lévi /Ivan Strenski -- Rethinking the Sacred: The Notions of ‘Human Body’ and ‘Territory’ in Conceptualizing Religion /Veikko Anttonen -- Giving Voice to the Sacred: Collaborative Representation in the Study of Living Religious Traditions /Lorne L. Dawson -- Encountering the Sacred: Saint Veneration and Visitational Dreams Among Moroccan Jews in Israel /Yoram Bilu -- The Numinous as a Category of Values /Dan Merkur -- The Sacred: A Sceptical View /Stewart Guthrie -- Understanding and Teaching Rudolph Otto’s The Idea of the Holy /Thomas A. Idinopulos -- The Domicile in the Study and Teaching of the Sacred, Using the Methodological Assumptions of Jonathan Z. Smith and Mircea Eliade /David Cave -- Theology and the Pedagogy of the Sacred /Charles E. Winquist -- Respect of Others’ Sacreds /George Weckman -- Select Bibliography /Thomas A. Idinopulos and Edward A. Yonan -- Index of Names /Thomas A. Idinopulos and Edward A. Yonan -- Index of Subjects /Thomas A. Idinopulos and Edward A. Yonan.